2014
DOI: 10.1371/journal.pone.0105084
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure of Mice to Dioxin Promotes Transgenerational Testicular Inflammation and an Increased Risk of Preterm Birth in Unexposed Mating Partners

Abstract: TCDD (2,3,7,8-tetrachlorodibenzo-p-dioxin, commonly known as dioxin) is a ubiquitous environmental contaminant and known endocrine disruptor. Using a mouse model, we previously found that adult female mice exposed in utero to TCDD (F1 generation) as well as multiple subsequent generations (F2-F4) exhibited reduced fertility and an increased incidence of spontaneous preterm birth. Additional studies revealed that male F1 mice with a similar in utero/developmental TCDD exposure also exhibited diminished fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 58 publications
4
46
0
Order By: Relevance
“…The similarities between the effects observed in the present study and those conducted by other investigators may be related to the mode of TCDD exposure. Bruner-Tran et al [57], in a study of mice exposed in utero to 10 g/kg TCDD, in three generations of study also observed significant alterations in these endpoints, confirming our results, demonstrating transgenerational impact inherited through the paternal germ line.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The similarities between the effects observed in the present study and those conducted by other investigators may be related to the mode of TCDD exposure. Bruner-Tran et al [57], in a study of mice exposed in utero to 10 g/kg TCDD, in three generations of study also observed significant alterations in these endpoints, confirming our results, demonstrating transgenerational impact inherited through the paternal germ line.…”
Section: Discussionsupporting
confidence: 92%
“…However, both experimental conditions, reduces fertility throughout life in exposed rat progeny to low doses of TCDD [16,56]. However, in a study carried out by Bruner-Tran et al [57] with adult female mice exposed in utero to 10 g/kg TCDD also exhibited reduced fertility in three-generation study, corroborating our results. Widely reported in the literature is a dose-response relationship in the reproductive function of rats exposed to TCDD doses during the intrauterine period [16,17,55,56,58], which may be related to its effects on the I/CL and consequently on the fertility of the animals from the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In another transgenerational study performed by another research group, exposure of pregnant mice to 10 [H9262]g/kg TCDD by gavage on gestation day 15.5 resulted in decrease in fertility and bias to preterm birth [83]: about 50% of F1–F3 males were sterile, 33–38% that were able to impregnate their mating female showed spontaneous delivery prior to E19.0. In all three generations of treated male mice there were signs of testicular inflammation and increased apoptosis of germ cells.…”
Section: Transgenerational Effects In Animal Experimentsmentioning
confidence: 99%
“…At 10-12 weeks, F2 females were mated to control males of similar age and monitored as above. Note: As previously described, like their siblings, F1 and F2 males exhibit subfertility [11, 157]. Perhaps as a consequence of reduced fertility in directly exposed animals, to date, mating of non-sibling F1 male and female mice or non-sibling F2 male and female mice has not resulted in offspring [103]; thus, toxicant exposed mice are necessarily mated to control partners.…”
Section: Methodsmentioning
confidence: 99%